The increase in bud load of Sauvignon Blanc affects the temporal dynamics of Botrytis bunch rot (botrytis cinerea) - Würz, Douglas André; Rufato, Leo; Brighenti, Alberto Fontanella (Revista de Ciências Agroveterinárias, 2025)
The objective of this work is to evaluate the effect of increasing bud load on the temporal dynamics of Botrytis bunch rot in Sauvignon Blanc vines. This work was conducted in the 2017 and 2018 harvests, in a commercial vineyard, in São Joaquim – SC. Sauvignon Blanc plants subjected to four different bud load levels were used: 15, 30, 50 and 75 buds/plant. The disease epidemic was evaluated using the variables: beginning of symptom appearance (BSA), time to reach maximum disease incidence and severity (TRMDI and TRMDS), maximum disease incidence and severity (Imax and Smax), and areas under disease incidence and severity progress curves (AUDIPC and AUDSPC). The increase in bud load, above 50 buds/plant, resulted in an increase in incidence and severity of the disease, in addition to AUDIPC and AUDSPC. There was an influence on the onset of symptoms, with the disease occurring early in plants with loads above 50 buds/plant. No effect was observed for the TRMDI and TRMDS variables. It is concluded that when adopting bud loads greater than 50 buds/plant, it is necessary to adopt complementary integrated disease management measures, to reduce the damage resulting from the occurrence of the disease.